Lumbar spine osteomyelitis and epidural abscess formation secondary to acupuncture - Godhania, Vinesh (J Surg Case Rep, 2016)
A 39-year-old male with no previous medical history presented with abdominal and low back pain. Based on clinical and radiological findings he was diagnosed with L1/L2 osteomyelitis and epidural abscess. Further history taking revealed recent use of acupuncture for treatment of mechanical back pain. The patient was treated conservatively with an extended course of antibiotics, monitored with repeat MRI scans and had a full recovery with no neurological deficit. This is the first reported case of epidural abscess formation and osteomyelitis after acupuncture in the UK. As acupuncture becomes more commonly used in western countries, it is important to be aware of this rare but serious complication.